Study guides

☆☆

Q: How solve x - 6 - x - 4 equals 10 - x?

Write your answer...

Submit

Still have questions?

Related questions

a + 4 = 10(a + 4) - 4 = 10 - 4a = 6

x-6-x-4=10-x-10=10-xx=20

2x - 4 = -10 2x = -10 +4 2x = -6 x = -3

x = 20

4x=-10 x=-2.5

A equals 4 because 4 plus 6 is 10 or 10 minus 6 is 4.

Solve:4 - 3x = 104 - 3x - 4 = 10 - 4-3x = 6-3x/-3 = 6/-3x = -2Check:4 - (3 x -2) = 104 - (-6) = 104 + 6 = 1010 = 10

3x-4=5x+6 gives: 2x=-10 which gives x=-5

3x+4=10 To solve: 3x+4=10 3x=6 x=2

10

-4 plus 10 equals 6.

3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x

3x+4 = 5x-6 3x-5x = -6-4 -2x = -10 x = 5

12g-6=6+4=10g

-4

8+2=10 6-2=4

To solve for x: 2x2 + 10 = 58 2x2 = 48 x2 = 24 x = √24 x = √4 × √6 x = 2√6

10

8x + 6 = 3x - 4 8x = 3x - 4 - 6 8x = 3x - 10 8x - 3x = -10 5x = -10 5x/5 = -10 x = -10/5 x = -2

Equals 10.

10

-x=-2

x=4 x=4

x = -8

10 + 4 = 14 10 x 4 = 40 10 - 4 = 6 or 4 - 10 = -6 so your answer is 6 or -6